2016
DOI: 10.3847/0004-637x/827/2/123
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Precession and Convection on the Dynamo Action

Abstract: To understand the generation of the Earth's magnetic field and those of other planets, we numerically investigate the combined effect of precession and convection on dynamo action in a spherical shell. Convection alone, precession alone, and the combined effect of convection and precession are studied at the low Ekman number at which the precessing flow is already unstable. The key result is that although precession or convection alone are not strong enough to support the dynamo action, the combined effect of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Obviously, as for even the most recent convectively driven dynamos (see, e.g., Schaeffer et al, 2017), the dimensionless parameters of our simulations, like the Reynolds and the Ekman numbers, remain far from the planetary ones: turbulence and dynamo thresholds have thus been reached by artificially increasing the amplitude of the mechanical forcings and of the magnetic Prandtl number, respectively. Note in particular that while the models of convectively driven and mechanically driven dynamos are often presented as antithetical, they could actually coexist and even collaborate to produce planetary magnetism (Wei, 2016), a behavior up to now largely unexplored. But we want to stress the following three points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, as for even the most recent convectively driven dynamos (see, e.g., Schaeffer et al, 2017), the dimensionless parameters of our simulations, like the Reynolds and the Ekman numbers, remain far from the planetary ones: turbulence and dynamo thresholds have thus been reached by artificially increasing the amplitude of the mechanical forcings and of the magnetic Prandtl number, respectively. Note in particular that while the models of convectively driven and mechanically driven dynamos are often presented as antithetical, they could actually coexist and even collaborate to produce planetary magnetism (Wei, 2016), a behavior up to now largely unexplored. But we want to stress the following three points.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the results presented here are expected to open new horizons and stimulate additional studies, that we hope will lead to rapid progress in our understanding of those mechanically-driven dynamos. Note in particular that while the models of convectivelydriven and mechanically-driven dynamos are often presented as antithetical, they could actually co-exist and even collaborate to produce planetary magnetism [Wei , 2016], a behavior up to now largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is also given here for precession energy contributing to driving the dynamo. Finally, a model based upon the combined effect of convection and precession, as the energy source of the geodynamo has already been proposed and suggests that neither source is adequate to drive the geodynamo alone [4].…”
Section: Introductionmentioning
confidence: 99%
“…They found that a stable stratification suppresses possible precessional instabilities, whereas an unstable stratification can lead to both stabilization and destabilization, depending on the parameters. This approach was later extended to the hydromagnetic case in Wei (2016), where it was shown that dynamos with a combined forcing are possible even when one forcing by itself leads to a failed dynamo. Here, we consider a non-uniform temperature stratification that is imposed by the temperature boundary conditions and we neglect the magnetic field.…”
Section: Introductionmentioning
confidence: 99%